GAYA DESAIN KOLONIAL BELANDA PADA INTERIOR GEREJA KATOLIK HATI KUDUS YESUS SURABAYA - Wardani, Laksmi Kusuma; Isada, Avelea (Institute of Research and Community Outreach - Petra Christian University, 2009)
The Church of the Sacred Heart of Jesus of Surabaya is one of the Dutch Catholic Church heritage buildings built in the 1920s. This church still exists today and its architecture and interior aspects remain significantly unchanged. This study aims to observe the characteristics of Dutch Colonial styles that have influenced the interior of this church. The results showed that the elements forming the existing space and furniture were influenced by the Dutch Colonial styles of design that flourished in Surabaya in the period of the 1900s to 1920s.